Addressing social resistance in emerging security technologies - Mitchener-Nissen, Timothy (Frontiers in Human Neuroscience, 2013)
In their efforts to enhance the safety and security of citizens, governments and law enforcement agencies look to scientists and engineers to produce modern methods for preventing, detecting, and prosecuting criminal activities. Whole body scanners, lie detection technologies, biometrics, etc., are all being developed for incorporation into the criminal justice apparatus. Yet despite their purported security benefits these technologies often evoke social resistance. Concerns over privacy, ethics, and function-creep appear repeatedly in analyses of these technologies. It is argued here that scientists and engineers continue to pay insufficient attention to this resistance; acknowledging the presence of these social concerns yet failing to meaningfully address them. In so doing they place at risk the very technologies and techniques they are seeking to develop, for socially controversial security technologies face restrictions and in some cases outright banning. By identifying sources of potential social resistance early in the research and design process, scientists can both engage with the public in meaningful debate and modify their security technologies before deployment so as to minimise social resistance and enhance uptake.